Absorption behavior of small biomolecules on carbon nanotube by density functional theory. Issue 169 (12th February 2016) - Xu, Yinye; Li, Dongxu; Xing, Jinchun
Abstract: Carbon nanotubes (CNTs) are famous one-dimensional function materials with important applications in energy storage and biomedicine industry. Biomolecules adsorbed in CNTs also have enormous potential in drug and gene delivery or disease supervision. With density functional theory, small biomolecules like H2 O and CO were packaged into CNTs, which was studied for their interaction and vibrational frequencies. Based on the results, electron density of CNTs would be weaken or dispersed with adsorption of small molecules, while no direct bonding can be observed in electron cloud. Typical vibrational frequencies of them could be used to characterized and distinguished easily both in simulation and experiments.